lllegal Financial Technology Loans Amid the Covid-19 Pandemic Problem - Nurharsya Khaer Hanafie; Andika A. Gani; Virmansyah Virmansyah (Universitas Negeri Semarang, 2022)
This study aims to identify and analyze illegal online lending practices in the midst of the Covid-19 problems. The research method used in this research is normative juridical research, namely the method of doctrinal legal research by reviewing the applicable regulatory provisions as a basis for analyzing the problems that occur and providing a paradigm as an effort to mitigate those problems. This qualitative research uses a descriptive analysis from primary and secondary legal materials through the study of documents and related literature. Based on the results of the study, the pandemic situation has resulted in growing illegal online loan services. Many individuals and micro, small and medium enterprises UMKM) are entangled in lending and borrowing due to the capital needs as a result of the Emergency Public Activity Restrictions (PPKM) policy. Based on the findings, the authors suggested that the improvement of public literacy related to lending needs to be encouraged, including efforts to ratify the personal data protection law and the drafting of the Fintech.